PENGARUH STRUKTUR MODAL DAN TINGKAT SUKU BUNGA TERHADAP PROFITABILITAS PADA PT. GUDANG GARAM Tbk. - Palempangan, Cristanto Yoga; Mongan, Benyamin; Jaya, Amir (FACULTY OF ECONOMICS AND BUSINESS FLORES UNIVERSITY, 2025)
This study aims to evaluate the impact of capital structure and interest rates on the profitability of PT Gudang Garam Tbk in the period 2014–2023. Bank Indonesia's basic interest rate and company annual financial reports are the data sources used. The findings of this research indicate that capital structure and interest rates do not have a significant influence on profitability. This indicates that PT Gudang Garam Tbk's profitability is more influenced by external factors such as industry regulations and production costs compared to capital structure and interest rates.